Tanggung Jawab Sekolah dalam Pendidikan Karakter Menuju Masyarakat Madani - Werdiningsih, Wilis (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
Every country dreams of a civil society. As an effort to realize a civil society, school as an educational institution has an important role, namely in the character education of children. Civil society is a social order with a social system that promotes democracy, civilization, tolerance for diversity over the principle of personal freedom and the stability of society with moral principles. Character education becomes an important thing to pay attention to, because children’s good character influences their behavior and children's goodbehavior becomes the capital for the formation of civil society. This study aims to examine the responsibilities of schools in character education to realize a civil society.The library research method is used through extracting information from various literatures related to character education and school responsibilities in character education towards civil society. The results show that schools have an important role in educating students who are characterized as part of today's society and as a determinant of the realization of civil society in the future. Therefore schools must really strengthen the educational process so that they can create the next generation of the nation who are intelligent and have good character.